Zatoichi's Pilgrimage Based on a Short Story by Kan Shimozawa - Ikehiro, Kazuo; Takeda, Senkichirô; Katsu, Shintaro; Yasuda, Michiyo; Tanaka, Kunie (Zatoichi: The Blind Swordsman Collection, 2019)
Troubled by his violent past, Zatoichi begins a journey to a series of shrines for a dose of cleansing spirituality. But as always, trouble isn't far behind, and the blind swordsman soon finds himself defending a widow from the self-interest of ruthless thugs and despicable townsfolk. Written by Kaneto Shindo (Onibaba), this fourteenth Zatoichi is a scathing attack on the upper classes and those who wield power, both in the criminal underworld and everyday society. [www.criterion.com]